1989
DOI: 10.1099/0022-1317-70-9-2439
|View full text |Cite
|
Sign up to set email alerts
|

The Immunoglobulin G Subclass Responses of Mice to Influenza A Virus: the Effect of Mouse Strain, and the Neutralizing Abilities of Individual Protein A-purified Subclass Antibodies

Abstract: SUMMARYThe IgG subclass responses to cold-adapted (ca) influenza A/Queensland/6/72 virus and purified haemagglutinin H3 was assessed in C57BL/6 and BALB/c mice. In BALB/c mice IgG2a was present as the major subclass in serum, lung and salivary secretions after two doses of ca virus. In contrast, the serum response in C57BL/6 mice was predominantly IgG1 after primary and secondary inoculations of ca virus. However, in lung and salivary secretions no specific subclass was dominant. When purified H3 was used as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
44
2

Year Published

1995
1995
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 33 publications
5
44
2
Order By: Relevance
“…In the 1980s several groups reported that IgG2a was the major antibody isotype conferring protection against viral infection and the most effective isotype for the induction of macrophage immunity in mice (1,2,8,10,19). Further studies confirmed that gamma interferon, which is induced by the type 1 CD4 ϩ Th1 response, stimulated the expression of IgG2a and inhibited the production of IgE.…”
Section: Discussionmentioning
confidence: 49%
“…In the 1980s several groups reported that IgG2a was the major antibody isotype conferring protection against viral infection and the most effective isotype for the induction of macrophage immunity in mice (1,2,8,10,19). Further studies confirmed that gamma interferon, which is induced by the type 1 CD4 ϩ Th1 response, stimulated the expression of IgG2a and inhibited the production of IgE.…”
Section: Discussionmentioning
confidence: 49%
“…The reason for the discrepancy between the results of Smucny et al (1995) and those of the present study is not entirely clear, but three possibilities could be considered. Firstly, the strain of mice used and secondly the age of the animals are both factors known to influence the murine antibody response due to biased T helper cell stimulation (Barrios et al, 1996 ;Hocart et al, 1989). Thirdly, there is increasing evidence to suggest that the dose of antigen, perhaps more than any other single factor, influences the cytokine profile of both naı$ ve (primary response) and differentiated (secondary response) T cells (Bretscher et al, 1992 ;Constant et al, 1995 ;Hosken et al, 1995), and thus, through cognate B cell-T cell interactions, the regulation of immunoglobulin isotype synthesis, including levels and specificities (Coffman et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…However, relatively few studies have compared the protective abilities of the different antiviral antibody IgG subclasses. Whereas some authors have shown that, in their models, the protection did not depend upon the IgG subclass of the antiviral antibodies (1,9,17,24), others, using either polyclonal antibodies or unrelated monoclonal antibodies, have observed that IgG2a displayed a stronger effect (2,13,18,21,28). However, differences in specificity and/or affinity could account for variations in neutralizing ability.…”
mentioning
confidence: 97%